Higher Winter-Spring Temperature and Winter-Spring/Summer Moisture Availability Increase Scots Pine Growth on Coastal Dune Microsites Around the South Baltic Sea - Janecka, Karolina; Harvey, Jill E.; Trouillier, Mario; Kaczka, Ryszard J.; Metslaid, Sandra; Metslaid, Marek; Buras, Allan; Wilmking, Martin (Frontiers in Forests and Global Change, 2020)
Coastal sand dunes near the Baltic Sea are a dynamic environment marking the boundary between land and sea and oftentimes covered by Scots pine (Pinus sylvestris L.) forests. Complex climate-environmental interactions characterize these ecosystems and largely determine the productivity and state of these coastal forests. In the face of future climate change, understanding interactions between coastal tree growth and climate variability is important to promote sustainable coastal forests. In this study, we assessed the effect of microsite conditions on tree growth and the temporal and spatial variability of the relationship between climate and Scots pine growth at nine coastal sand dune sites located around the south Baltic Sea. At each site, we studied the growth of Scots pine growing at microsites located at the ridge and bottom of a dune and built a network of 18 ring width and 18 latewood blue intensity tree-ring chronologies. Across this network, we found that microsite has a minor influence on ring width variability, basal area increment, latewood blue intensity, and climate sensitivity. However, at the local scale, microsite effects turned out to be important for growth and climate sensitivity in some sites. Correlation analysis indicated that. the strength and direction of climate-growth responses for the ring width and blue intensity chronologies were similar for climate variables over the 1903-2016 period. A strong and positive relationship between ring width and latewood blue intensity chronologies with winter-spring temperature was detected at local and regional scales. We identified a relatively strong, positive influence of winter-spring/summer moisture availability on both tree-ring proxies. When climate-growth responses between two intervals (1903-1959, 1960-2016) were compared, the strength of growth responses to temperature and moisture availability for both proxies varied. More specifically for the ring-width network, we identified decreasing temperature-growth responses, which is in contrast to the latewood blue intensity network, where we documented decreasing and increasing temperature-growth relationships in the north and south respectively. We conclude coastal Scots pine forests are primarily limited by winter or winter-spring temperatures and drought despite differing microsite conditions. We detected some spatial and temporal variability in climate-growth relationships that warrant further investigation.